PENGARUH PENETAPAN HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR MEREK HONDA DI DHARMASRAYA - Nandiroh, Nandiroh; Yulihardi, Yulihardi; Yolamalinda, Yolamalinda (Pendidikan Ekonomi, 2013)
ABSTRACTÂ The research was conducted in Dharmasraya, the influence of pricing and promotion on purchase decisions. Research time in July of 2013. Data processing techniques performed using multiple linear regression analysis using SPSS version 16. Defined samples studied were 105 respondents. Sampling techniques using sampling techniques Claster.Regression test results show that all the independent variables (price and promotion) positive influence on purchasing decisions. Greatest positive influence on purchase decisions of Honda motorcycles in Dharmasraya is the variable (XI) as indicated by the regression coefficient of 0.559, then followed by a promotion variable (X2) of the indicated value of the regression coefficient of 0.117. From the results of this study suggested that the price has the most dominant influence on Consumer Purchase Decision, expected the company to defend it. For promotional variables did not significantly affect Consumer Buying Decision expected the company to increase it so as not to be outdone by other competitors.Â Keywords: Price, Promotion and Purchasing Decisions